A Systematic Review of Therapeutic Interventions and Management Strategies for Gulf War Illness. Issue 1 (30th January 2021) - Nugent, Shannon M; Freeman, Michele; Ayers, Chelsea K; Winchell, Kara A; Press, Ashlyn M; O'Neil, Maya E; Paynter, Robin; Kansagara, Devan
ABSTRACT: Introduction: After the 1990 to 1991 conflict in the Persian Gulf, many Gulf War Veterans began reporting numerous unexplained symptoms including, but not limited to, systemic pain, fatigue, flu-like symptoms, and difficulty with memory/concentration. These symptom clusters are now referred to as Gulf War Illness (GWI). Although the etiology of GWI is still debated, as many as 250, 000 former service members have been continually suffering from GWI since 1991, making the need for treatment urgent. A broad variety of treatments have been considered for GWI, but there has not been a broad and comprehensive assessment of what is known and not known about GWI treatment. We conducted a systematic review to catalogue the types of treatments that have been examined for GWI, to evaluate the effectiveness and harms of these interventions, and to identify promising and ongoing areas of future GWI treatment research. Materials and Methods: We searched electronic databases, trial registries, and reference lists through September 2019 for randomized controlled trial and nonrandomized controlled trial and cohort studies directly comparing interventions for Veterans with GWI to each other, placebo, or usual care. We abstracted data on study design, demographics, interventions, and outcomes. Two reviewers independently assessed studies for inclusion, quality, and strength of evidence (SOE) using prespecified criteria. We resolved discordant ratings by discussion and consensus. Results: We identified 12 randomized controlled trials, each of which examined a different intervention for GWI. We found moderate SOE that cognitive behavioral therapy and exercise, separately and in combination, were associated with improvements in several GWI symptom domains. There was low SOE of benefit from two mindfulness-based interventions and continuous positive airway pressure (CPAP). Mindfulness-based stress reduction improved pain, cognitive functioning, fatigue, depression, and posttraumatic stress disorder (PTSD), whereas mind-body bridging improved fatigue, depression, posttraumatic stress disorder, and sleep, although pain and other outcomes did not improve. Continuous positive airway pressure improved overall physical health, pain, cognitive functioning, fatigue, mental health, and sleep quality in a small study of Veterans with sleep-disordered breathing and GWI. We found moderate SOE that doxycycline is ineffective for GWI in mycoplasma DNA-positive Veterans and increases the risk of adverse events compared with placebo. We also found 33 ongoing, single-arm pilot, or unpublished studies examining a variety of interventions. Conclusion: Cognitive behavioral therapy (moderate SOE), exercise (moderate SOE), and mindfulness-based interventions (low SOE) may be effective in improving several symptom domains in patients with GWI. Doxycycline was ineffective and associated with harms (moderate SOE). Larger, more rigorous studies are needed to confirm the benefits found in completed trials. A wide array of treatments are being assessed in ongoing trials. A sufficient evidence base will need to be developed to guide clinicians about which treatments are most likely to be effective in clinical practice and which treatments should be avoided.